Freeze-or-flight? Neural rhythms in the mPFC-Amygdala network predict the selection of dimorphic defensive behaviors - 한효빈; Choi Ji Hyun (Jee H Choi) (The 24th Annual Meeting of the Korean Society for Brain and Neural Sciences, 2021)
When faced with a threat (e.g., confronting a predator), our brain quickly evaluates relevant behavioral strategies to choose among different types of defensive behavior (e.g., freezing, escaping). Recent studies established a causal relationship between freezing and theta (5 Hz) rhythms in mPFC and BLA (basolateral amygdala). However, the neural mechanism for defensive behaviors remains largely elusive. Here, we present an extended framework suggesting the dynamic interplay in mPFC-BLA oscillations that play a key role in the selection of defensive behavior. Using predator-escape paradigm with mouse EEG, we observed how freezing due to fear recruits low-theta (5 Hz) rhythm in mPFC and BLA, while escaping recruits high-theta (8-12 Hz) and beta (30 Hz) rhythm. Most importantly, the emergence of one type of theta entails the suppression of the other. We found that two types of theta rhythm barely coexist (~1%, chance = 4%), and go through abrupt transition rather than a gradual shift in peak frequency. Effective connectivity analysis reveals each rhythm represents a distinct flow of information during each fear response: for freezing, mPFC？？？BLA at low-theta, and for escaping, BLA？？？mPFC at high-theta and mPFC？？？BLA at beta. During the resting state after the threat period, the theta- and beta-rhythmic functional networks in mPFC-BLA circuit were suppressed, and the gamma (40-70 Hz) network was activated. Our findings not only show a role of mPFC-BLA circuit as a potential hub in control of defensive behaviors, but also provide how oscillatory dynamics support it.